Utilization of Virtual Reality (VR) for Employee Training in Indonesia: A Systematic Literature Review - Nyoto, Nyoto; Nyoto, Rebecca La Volla; Renaldo, Nicholas (Luxury: Landscape of Business Administration, 2025)
This study aims to examine the trends and implementation of Virtual Reality (VR) in employee training in Indonesia through a systematic literature review of 18 articles published between 2020 and 2025. The analysis shows that the use of VR in employee training began to develop in 2020 and has increased rapidly in the past five years. VR applications span various sectors such as construction, energy, healthcare, fintech, MSMEs, and tourism. The types of training developed include technical simulations, occupational safety, soft skills development, leadership, and disaster preparedness. Furthermore, recent trends show the integration of VR with other technologies such as Artificial Intelligence and Augmented Reality. These findings confirm that VR has become a strategic approach in developing employee competencies across sectors in Indonesia.